Integrating human resource management in urban workforce development: A focus on salary increments - L. Yu; A. Santos (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: This study investigates the impact of demographic factors and skill enhancements on salary increments at Guangzhou Wangming Water Joy Design Co., Ltd., a leading Chinese company in the water park equipment sector using Light-Resin Transfer Molding technology. It aims to propose targeted strategies for boosting employee welfare and enhancing the company's competitive edge and organizational success.METHODS: Employing a quantitative descriptive research approach, the study collected data through survey questionnaires from 224 employees, including 196 teachers and 28 supervisors. The analysis involved calculating percentages and frequencies to describe respondent demographics and using weighted means to assess factors influencing salary increments and employee welfare.FINDINGS: Founded in 2006 and now operating in over 30 countries, the company demonstrates a significant global presence. Workforce analysis revealed a predominantly male demographic (63.33%) and a significant concentration of employees aged 36-45 years (83.33%), indicative of a mature and experienced employee base. Crucially, skill enhancement correlated strongly with salary progression, and structured professional development was linked to high employee satisfaction. Key measures included a mean satisfaction rating of 4.15 for work-life balance initiatives and a mean effectiveness rating of 4.20 for training programs.CONCLUSION: Based on the findings, it is recommended that the company integrate historical narratives into employee training programs to foster organizational pride and loyalty. Furthermore, expanding diversity and inclusion efforts, emphasizing continuous learning, enhancing welfare programs, and instituting adaptive feedback mechanisms are essential for addressing the complexities of employee demographics and improving salary increment practices. These strategies are vital for promoting employee welfare and reinforcing the company's competitive stance in the global market.